Student Consumerism Attitudes towards Higher Education - Raden Johnny Hadi Raharjo; G. Oka Warmana; Anandya Zalva Yunnafisah; Andrew Baihaqi Firdaus (Nusantara Science and Technology Proceedings, 2022)
Contemporary society contends that consumption is the backbone of our way of life. It is not solely an indicator of an individual or group's social standing, but also functions as a means of addressing issues, creating significance in our surroundings, and even developing personal identities. The ubiquitous influence of consumerism has broadened the definition of commodities to include non-tangible services. When services become commodities, providers tend to prioritize consumer service-oriented activities to attract and retain clients driven by market ideology. This model has been adopted by higher education institutions, such as universities, resulting in consumerist behavior by students seeking educational products and services. Therefore, this study aims to examine student consumerist behavior. A quantitative methodology was employed, and the sample consisted of 500 respondents. The survey revealed that students exhibit consumerist tendencies regarding the educational services offered by universities. Consumerism is linked to lecturer expectations, job readiness, and grades, but not student accountability.